Integrative behavioral couple therapy. (February 2017) - Christensen, Andrew; Doss, Brian D
Highlights: Integrative Behavioral Couple Therapy (IBCT) broadens the traditional behavioral theory of couple distress and of intervention. Three clinical trials support the efficacy of IBCT. IBCT has been successfully disseminated throughout the VA. A large, nationwide clinical trial demonstrated the positive impact of OurRelationship.com, an 8-hour online program based on IBCT. Abstract : Integrative Behavioral Couple Therapy (IBCT) is based in part on traditional behavioral couple therapy but expands both the conceptualization of couple distress and of intervention. The efficacy of IBCT has been supported in three clinical trials, including one with five year follow-up. Additionally, the effectiveness of IBCT in the real world has been supported through a system-wide dissemination effort in the United States Department of Veteran's Affairs. The reach of IBCT has also been extended through an online program, www.OurRelationship.com, based on IBCT. A nationwide clinical trial with a representative sample of the US population demonstrated the effectiveness of this program on both relationship and individual variables.